Involvement of a Multidrug Efflux Pump and Alterations in Cell Surface Structure in the Synergistic Antifungal Activity of Nagilactone E and Anethole against Budding Yeast Saccharomyces cerevisiae - Yuki Ueda; Yuhei O. Tahara; Makoto Miyata; Akira Ogita; Yoshihiro Yamaguchi; Toshio Tanaka; Ken-ichi Fujita (MDPI AG, 2021)
Nagilactone E, an antifungal agent derived from the root bark of Podocarpus nagi, inhibits 1,3-β glucan synthesis; however, its inhibitory activity is weak. Anethole, the principal component of anise oil, enhances the antifungal activity of nagilactone E. We aimed to determine the combinatorial effect and underlying mechanisms of action of nagilactone E and anethole against the budding yeast Saccharomyces cerevisiae. Analyses using gene-deficient strains showed that the multidrug efflux pump PDR5 is associated with nagilactone E resistance; its transcription was gradually restricted in cells treated with the drug combination for a prolonged duration but not in nagilactone-E-treated cells. Green-fluorescent-protein-tagged Pdr5p was intensively expressed and localized on the plasma membrane of nagilactone-E-treated cells but not in drug-combination-treated cells. Quick-freeze deep-etch electron microscopy revealed the smoothening of intertwined fiber structures on the cell surface of drug-combination-treated cells and spheroplasts, indicating a decline in cell wall components and loss of cell wall strength. Anethole enhanced the antifungal activity of nagilactone E by enabling its retention within cells, thereby accelerating cell wall damage. The combination of nagilactone E and anethole can be employed in clinical settings as an antifungal, as well as a food preservative to restrict food spoilage.